2018
DOI: 10.29252/jabr.05.04.04
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Synthesis of Silver Nanoparticles by Mango Plant Extract and Its Anti-Candida Effects

Abstract: Introduction: In recent years, using plant products alone and along with metal nanoparticles has been widely considered in preventing or killing pathogens including fungi. Increasing the use of chemical drugs has increased the resistance of pathogenic fungi. The present study aimed at investigating the biological synthesis of silver nanoparticles by mango plant extract and its anti-Candida effects. Materials and Methods: First, the Indian mangoes were bought from the Isfahan fruit and vegetable market and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…MFC values of these AgCl-NPs were 80 and 100 µ g/mL for C. glabrata and C. albicans, respectively ( Figure 7B). These results were in agreement with Salati et al [42], who investigated biological synthesis of AgNPs by a mango plant extract, and their anti-Candida effects. They reported that biogenic AgNPs were most effective against C. glabrata as compared to C. albicans.…”
Section: Determination Of Mic Mbc and Mfc Valuessupporting
confidence: 92%
“…MFC values of these AgCl-NPs were 80 and 100 µ g/mL for C. glabrata and C. albicans, respectively ( Figure 7B). These results were in agreement with Salati et al [42], who investigated biological synthesis of AgNPs by a mango plant extract, and their anti-Candida effects. They reported that biogenic AgNPs were most effective against C. glabrata as compared to C. albicans.…”
Section: Determination Of Mic Mbc and Mfc Valuessupporting
confidence: 92%
“…The secretion of hydrolytic enzymes is reported to play an important role in the pathogenicity of Candida. The adhesions, lipases and Saps are encoded by LIP and SAP genes (SAPT1-4), respectively [42]. Metwally et al [43] stated that lipase gene expression was reduced by Pluchea dioscoridis leaf extract from 100% to 7% and 19% than that obtained from untreated A. niger as documented by quantitative RT-PCR analysis, and consequently the lipase enzyme activity that play a role in the pathogenecity of A. niger in otomycosis infection.…”
Section: Real Time Pcr Quantification Of Lip1 Expressionmentioning
confidence: 99%
“…Several studies have reported mango seed kernels for anti-enteric [ 12 ], antibacterial [ 13 ], antidiarrheal, anti-salmonella [ 14 ], and antioxidant properties [ 15 ]. The AgNPs have been effectively biosynthesized using various parts of the mango, including the peel [ 16 ], leaves [ 17 ], the flower [ 18 ], and the kernel [ 19 ]. However, AgNPs synthesis using mango kernels for efficacy against Shigella species is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%